GENETICA DA AQUIROPODIA. III. AVERIGUACAO - Freire Maia, A. (My University, 1974)
The processes used to ascertain acheiropodia in Brazil as well as in Portugal are described. Several patients were found in Brazil, all of them of Portuguese ancestry, but no case was found in Portugal or in the Portuguese literature. Several cases which, in various ways, were described as 'similar' to information about the families studied is given, with clinical information about two premature acheiropods.
The handless and footless families in Brazil